1997
DOI: 10.1080/00288233.1997.9513249
|View full text |Cite
|
Sign up to set email alerts
|

Effects and interactions of phosphorus and sulphur on a mown white clover/ryegrass sward 3. Indices of nutrient adequacy

Abstract: Relationships were examined between relative yields of pasture with respect to phosphorus (P) and sulphur (S) applications, and clover herbage P and S concentrations and P/nitrogen (N) and S/N ratios in a P x S factorial fertiliser trial on a mown clover/ryegrass sward. The relationships between the yield of a treatment relative to the maximum yield obtainable with high rates of P alone (RY[P]) and both % P and P/N were affected by the application rate of S. S deficiency generally lowered the % P required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Clover S/N followed the same general trend over time for all treatments as clover S/P. Clover 100 S/ N ratios were lower than the optimum range of 4.8-5.0 (for 95%-98% RY) for adequate S nutrition (Sinclair et al 1997) for all treatments except the high residual S fertilisers, for most of the period over which they were measured ( Fig. 2B).…”
Section: Clover S/n Ssp Tsp 15ss 22ss and High Residualsmentioning
confidence: 64%
See 1 more Smart Citation
“…Clover S/N followed the same general trend over time for all treatments as clover S/P. Clover 100 S/ N ratios were lower than the optimum range of 4.8-5.0 (for 95%-98% RY) for adequate S nutrition (Sinclair et al 1997) for all treatments except the high residual S fertilisers, for most of the period over which they were measured ( Fig. 2B).…”
Section: Clover S/n Ssp Tsp 15ss 22ss and High Residualsmentioning
confidence: 64%
“…From recent research at an adjacent site, nutrient ratios in clover for balanced (e.g., S/P) and adequate (e.g., S/N) nutrition have been determined (Sinclair et al 1996a(Sinclair et al , 1996b(Sinclair et al , 1997. The use of different S fertilisers could result in different clover S/P and S/N ratios.…”
Section: Introductionmentioning
confidence: 99%
“…They are also important in relation to litter decomposition and mineral cycling under different input managements. It has been suggested that shoot nutrient concentrations or ratios may be a better indicator of nutrient status than soil nutrient concentrations (Sinclair et al 1997). The approach of this study is that each species has a particular niche within the range of environmental and management conditions in the high country and that, accordingly, it may be necessary to define the shoot nutrient concentrations for a range of different species.…”
Section: Introductionmentioning
confidence: 99%
“…Salette and Huché (1991) extended this approach to other nutrients such as P and K. Because of the similarities in the decrease in N and P concentrations with increasing shoot biomass, it was proposed to use the P:N ratio for diagnostic purposes (Salette and Huché 1991;Duru 1992;Duru and Ducrocq 1997). The use of P:N ratio to detect the nature of nutrient limitations was also proposed by Koerselman and Meuleman (1996) on natural ecosystems in the Netherlands and by Sinclair et al (1997) on cut white clover/ryegrass swards in New Zealand.…”
mentioning
confidence: 99%